Caracterización de los contaminantes físicos y químicos presentes en el Río Yanayacu del cantón Salcedo, 2013 - Pullotasig Toasa, Blanca Alicia (2014)
In this paper the analysis of the physical and chemical properties of water Yanayacu River located in the province of Cotopaxi Region Salcedo, Yacayacu Guapante neighborhood is established. Systematic sampling, in which he had a significant number of samples taken at different points of the aforementioned river, ran. Obtaining information will be performed to determine the data necessary for the support of research regarding the analysis will serve for pollution levels containing in its causal for comparison with the Standard INEN 1108, which speaks of water requirements safe for human consumption. In chapter I referred to the theoretical research that sustains the research is done, it is structured based on the fundamental categories. In Chapter II the methodologies used are evident, the same as a support medium for methodological, systematic, and related logical approach leading research in order to find the way, the tools and methodological directions conducive to developing the proposal Additional qualitative and quantitative expressions of the result for comparison with their respective INEN 1108 standard for drinking water are indicated….